Fabrication of Mesoporous Silica-coated Graphene Oxide by New Method and Application in Solid Phase Extraction for Preconcentration of Cu2+ - Ali Moghimi (Journal of Chemical Health Risks, 2018)
Graphene oxide is a derivates of graphene that has a ultrahigh specific surface space with variety of chemically reactive functionalities, such as epoxy and hydroxyl groups on the basal plane and carboxylic acid groups along the area edge, which can be use different groups for functionalization, consequentlyit has a great promise for use as sorbent materials. On the other hand silica is well-known one of the best sorbent for adsorption that we use it as substance for coated on the graphene oxide for produce an ultra-sensitive sorbent. A new technique using a solid phase extraction (SPE) cartridge with graphene oxide functionalized by silica as sorbent was developed for the preconcentration of trace amounts of copper and was determined by flame atomic absorption spectrometry (FAAS). Some of the important parameters were selected and optimized. Under the optimized conditions the limit of detection (LOD) and limit of quantification (LOQ) were 0.175, 0.585 and the proposed method has a good reproducibility 0.85% (RSD %). The enrichment factor was 200 and the percentage of recovery was in the range of 97-100% .The method was successfully applied to the recovery of Cu2+ in different type of water samples. Graphene oxide and its derivates such as GO@SiO2 in this study are full of potential to use as an excellent adsorbent in the extraction method like solid phase extraction (SPE).